Welfare - "Barry, Norman" (New Delhi, 2002)
This book covers the following topics The idea of welfare in political thought; Utilitarianism and the origins of Welfare philosophy; Anti- individualism: From the minimal state to the welfare state; Liberal political Economy and welfare; The Critique of individualism and the Ethics of welfare; Justice, Equality and welfare; Welfare the welfare state and politics etc.
Keywords: Economics - political aspects